Determination of Economic Injury Levels of Maruca vitrata in Mungbean (Journal of Agriculture & Rural Development, 2008)
Maruca vitrata is considered to be one of the major pests of mungbean. The damage potential and economic threshold levels of Maruca vitrata larvae on mungbean were worked out at ARS, BARI, Burirhat, Rangpur during rabi 2005-2006 and 2006-2007. On an average single larva per m row reduced the yield to the extent of 154 kg/ha and 106 kg/ha in 2005-2006 and 2006-2007 cropping seasons, respectively. The ratio of the value of yield saved to the cost of insecticide application at one larva per m row in 2005-2006 was 1.45 and same in 2006-2007 was 1.34. EIL for Maruca vitrata were determined as 1.0 and 1.16 larvae per m row in 2005-2006 & 2006-2007respectively. ET value was determined from EILs and those were found to be at 0.75 and 0.87 larvae per m row in 2005-2006 & 2006-2007 respectively. On the basis of means of two years the EIL and ETL values of Maruca vitrata were 1.08 & 0.81 larvae per m row, respectively. Key words: ETL, EIL, Maruca vitrata, Mungbean. doi:10.3329/jard.v6i1.1662 J Agric Rural Dev 6(1&2), 91-97, June 2008